2019
DOI: 10.1177/0009922819848080
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones and Text Messaging are Associated With Higher Parent Quality of Life Scores and Enrollment in Early Intervention After NICU Discharge

Abstract: The purpose of this study was to evaluate the impact of access to communication technology on caregiver quality of life, neurodevelopmental, and medical outcomes (eg, rehospitalization, emergency room visits, or surgeries) in preterm infants, and enrollment in public assistance programs. In this cross-sectional study, we surveyed families of preterm infants in a high-risk infant-follow-up clinic. We estimated associations of access to various modes of communication technology with outcomes, adjusting for socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We included six qualitative studies and most (4/6) were conducted with neonatal or pediatric critical care populations. Caregivers were most commonly parents (n = 19, 61%) [ 30 , 31 , 33 , 35 38 , 41 44 , 47 49 , 51 , 52 ] and unspecified family caregivers more broadly—which could include parents, but the term was more broadly defined (n = 7, 23%) [ 23 , 24 , 26 , 27 , 32 , 39 , 50 ]. One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…We included six qualitative studies and most (4/6) were conducted with neonatal or pediatric critical care populations. Caregivers were most commonly parents (n = 19, 61%) [ 30 , 31 , 33 , 35 38 , 41 44 , 47 49 , 51 , 52 ] and unspecified family caregivers more broadly—which could include parents, but the term was more broadly defined (n = 7, 23%) [ 23 , 24 , 26 , 27 , 32 , 39 , 50 ]. One study was specific to mothers [ 40 ] and one study was specific to fathers [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by our group described the impact of preterm birth on parents and families and identified associated modifiable factors [ 41 ]. We also identified that access to email, text messaging, and smartphones was associated with higher parental quality of life [ 15 ]. In addition McAndrews et al also described an association between extremely preterm infants and worse HRQOL during the NICU hospitalized but with more improvement after discharge than others hospitalized in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…A 150-item questionnaire developed for this study was administered to participants about life after discharge from the NICU ( Supplemental Material ). Patient recruitment, survey administration and population characteristics are detailed in previous work [ 15 , 16 ]. The Institutional Review Board at the center approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…A 150-item questionnaire with components validated in English and Spanish was administered to participants about life after discharge from the NICU.. Patient recruitment, survey administration and population characteristics are detailed in previous work [ 19 , 20 ]. The Institutional Review Board at Children’s Hospital Los Angeles approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%